Necator americanus Ancylostoma Secreted Protein-2 (Na-ASP-2) Binds an Ascaroside (ascr#3) in Its Fatty Acid Binding Site - El Atab, Ola; Darwiche, Rabih; Truax, Nathanyal J.; Schneiter, Roger; Hull, Kenneth G.; Romo, Daniel; Asojo, Oluwatoyin A. (Frontiers in Chemistry, 2020)
During their infective stages, hookworms release excretory-secretory (E-S) products, small molecules, and proteins, to help evade and suppress the host's immune system. Small molecules found in E-S products of mammalian hookworms include nematode derived metabolites like ascarosides, which are composed of the sugar ascarylose linked to a fatty acid side chain. The most abundant proteins found in hookworm E-S products are members of the protein family known as Ancylostoma secreted protein (ASP). In this study, several ascarosides and their fatty acid moieties were synthesized and tested for in vitro binding to Na-ASP-2 using both a ligand competition assay and microscale thermophoresis. The fatty acid moieties of all ascarosides tested and ascr#3, an ascaroside found in rat hookworm E-S products bind to Na-ASP-2's palmitate binding cavity. These molecules were confirmed to bind to the palmitate but not the sterol binding sites. An ascaroside, oscr#10 which is not found in hookworm E-S products, does not bind to Na-ASP-2. More studies are required to determine the structural basis of ascarosides binding by Na-ASP-2 and to understand the physiological significance of these observations.